Impact of Computer Assisted Instruction (C.A.I.) on Academic Behaviour of Computer Science Students at Ajayi Crowther University, Oyo State, Nigeria. - Oluwaseyi Aina Gbolade Opesemowo; Damilare Andrew Omideyi (Studies in Learning and Teaching, 2023)
The impact of computer assisted instruction (C.A.I.) on the academic performance of computer science students at Ajayi Crowther University, Oyo was examined. The study investigated the post-test scores of both the control and experimental groups and the effect of pre-test scores on students taught using the traditional lecture method. Quasi-experimental study design was adopted; a pre-test and post-test were conducted for the sample groups. Simple random sampling technique was used to select 50 participants for the study. The instrument was administered twice, i.e., the pre-test and post-test. The pre-test was conducted on both the experimental and control groups, and both groups were presented with the post-test to ascertain the effectiveness of the C.A.I. The instrument’s reliability yielded a coefficient of 0.78 Cronbach alpha. Data were analysed using an independent t-test. Results demonstrated that there was a statistically significant difference between the mean score (t = 1.20, df = 38, p > 0.05) of students taught using the conventional lecture method (control) and students exposed to C.A.I. (experimental). Based on the results, it was recommended that using C.A.I. for teaching and learning should be encouraged at Ajayi Crowther University, Oyo, Nigeria.